Modeling a Nociceptive Neuro-Immune Synapse Activated by ATP and 5-HT in Meninges: Novel Clues on Transduction of Chemical Signals Into Persistent or Rhythmic Neuronal Firing - Suleimanova, Alina; Talanov, Max; Gafurov, Oleg; Gafarov, Fail’; Koroleva, Ksenia; Virenque, Anaïs; Noe, Francesco M.; Mikhailov, Nikita; Nistri, Andrea; Giniatullin, Rashid (Frontiers in Cellular Neuroscience, 2020)
Extracellular ATP and serotonin (5-HT) are powerful triggers of nociceptive firing in the meninges, a process supporting headache and whose cellular mechanisms are incompletely understood. The aim of the current study was to develop, with the neurosimulator NEURON, a novel approach to explore in silico the molecular determinants of the long-lasting, pulsatile nature of migraine attacks. The present model included ATP and 5-HT release, ATP diffusion and hydrolysis, 5-HT uptake, differential activation of ATP P2X or 5-HT3 receptors, and receptor subtype-specific desensitization. The model also tested the role of branched meningeal fibers with multiple release sites. Spike generation and propagation were simulated using variable contribution by potassium and sodium channels in a multi-compartment fiber environment. Multiple factors appeared important to ensure prolonged nociceptive firing potentially relevant to long-lasting pain. Crucial roles were observed in: i) co-expression of ATP P2X2 and P2X3 receptor subunits; ii) intrinsic activation/inactivation properties of sodium Nav1.8 channels; iii) temporal and spatial distribution of ATP/5-HT release sites along the branches of trigeminal nerve fibers. Based on these factors we could obtain either persistent activation of nociceptive firing or its periodic bursting mimicking the pulsating nature of pain. In summary, our model proposes a novel tool for exploration of peripheral nociception to test the contribution of clinically relevant factors to headache including migraine pain.